Genetic determinants of antibiotic resistance in enterobacteria isolated during microbiological monitoring in the perinatal center - A. V. Ustyuzhanin; G. N. Chistyakova; I. I. Remizova; A. A. Makhanyok (Эпидемиология и вакцинопрофилактика, 2023)
Relevance. Currently, studies of the prevalence of antibiotic resistance and its genetic characteristics are focused primarily on the adult population, although infection with multiple drug infection has been registered as etiological agents of a general infection in obstetric and gynecological and pediatric institutions. The study of the prevalence of genetic determinants of antibiotic resistance is an important area of scientific research.Aim. To analyze the results of the studies carried out to identify the genetic determinants of antibiotic resistance of enterobacteria isolated during microbiological monitoring in the perinatal center.Materials and methods. The genetic profile of antibiotic resistance was studied in ESBL-producing strains isolated from 45 women and 35 children examined at the departments of the Federal State Budgetary Institution «NII OMM» of the Ministry of Health of Russia. To determine the determinants of antibiotic resistance, 80 non-duplicate strains of 7 species of the Enterobacteriaceae family were studied. DNA of bacterial cells was isolated from a daily culture of microorganisms using the PROBA-NK kit, detection of the tem, ctx-M-1, shv genes; oxa-40-like, oxa-48-like, oxa-23-like, oxa-51-like, imp, kpc, ges, ndm, vim were carried out using the diagnostic kit «BacResista GLA» on the detecting amplifier DT-48 (DNA -technology, Russia). To assess the statistical significance of differences in the frequency of occurrence of genes, Pearson's c2 test with Yates' correction was used.Results and discussion. When analyzing the results of studies on the molecular genetic detection of antibiotic resistance determinants, which we conducted in 2022, it was found that 8 genovariants were found in bacterial strains isolated from patients of the departments of the Research Institute of OMM in Yekaterinburg, providing resistance to beta-lactam antibiotics. The dominant genome, as in 2021, remains blaCTX-M-1, found in 29 cases. The blaTEM gene was identified both in association with other genes and as a single variant in Escherichiae coli and Klebsiella pneumoniae strains. Of the eight strains of K. pneumoniae, 4 were found to have three antibiotic resistance genes blaCTX-M, blaTEM, blaSHV, strains with a genetic profile of blaCTX-M, blaTEM, blaSHV, blaNDM were isolated once; and blaTEM, blaSHV, blaKPC. In one strain of K. pneumoniae, phenotypically showing resistance to AB, no genetic determinants of AB resistance were found. In addition to resistance to beta-lactam antibiotics, the strains demonstrate resistance to such groups of antibacterial drugs as fluoroquinolones, phosphonic acid derivatives (fosfomycin), and aminoglycosides. The data obtained indicate that the intestines of newborns during their stay at the stationary stage of nursing in some cases are colonized by strains of enterobacteria with multidrug resistance. Consequently, children are a reservoir of resistant microorganisms and can be sources of pathogens of infectious diseases in families and children's organized groups.